The urban syndemic of COVID-19: insights, reflections and implications: Cities, health and COVID-19: editorial for the special issue. (21st July 2021) - Ellis, Geraint; Grant, Marcus; Brown, Caroline; Teixeira Caiaffa, Waleska; Shenton, Fiona C.; Lindsay, Steven W.; Dora, Carlos; Nguendo-Yongsi, Hénock Blaise; Morgan, Sue
ABSTRACT: This editorial introduces the origin, purpose and scope of a Special Issue on COVID-19. It brings together 43 contributions from across the globe that examine the way in which COVID-19 has challenged the way we think about urban design, spatial planning and city governance. The editorial draws out a number of key messages from this body of work, highlighting how the impact of COVID-19 has been most devastating when combined with the existing vulnerabilities and chronic ill-health experienced in pre-pandemic cities. Following The Lancet, we, therefore, characterise this as a syndemic rather than pandemic, due to the way it interacts with existing urban NCDs. This provides further resolve to address long-standing urban health inequalities and challenges, while seeking more holistic ways of addressing these, for example through the Sustainable Development Goals. The editorial explains the role of our partners in the Special Issue (ISUH, Design Council and BOVA Network), draws out some of the themes from the collected papers, and finally highlights an agenda for future contributions to Cities & Health that will allow us to better understand and respond to the aftermath of the COVID-19 syndemic.